Kombucha Tea-associated microbes remodel host metabolic pathways to suppress lipid accumulation. - Rachel N DuMez-Kornegay; Lillian S Baker; Alexis J Morris; Whitney L M DeLoach; Robert H Dowen (PLoS Genetics, 2024)
The popularity of the ancient, probiotic-rich beverage Kombucha Tea (KT) has surged in part due to its purported health benefits, which include protection against metabolic diseases; however, these claims have not been rigorously tested and the mechanisms underlying host response to the probiotics in KT are unknown. Here, we establish a reproducible method to maintain C. elegans on a diet exclusively consisting of Kombucha Tea-associated microbes (KTM), which mirrors the microbial community found in the fermenting culture. KT microbes robustly colonize the gut of KTM-fed animals and confer normal development and fecundity. Intriguingly, animals consuming KTMs display a marked reduction in total lipid stores and lipid droplet size. We find that the reduced fat accumulation phenotype is not due to impaired nutrient absorption, but rather it is sustained by a programed metabolic response in the intestine of the host. KTM consumption triggers widespread transcriptional changes within core lipid metabolism pathways, including upregulation of a suite of lysosomal lipase genes that are induced during lipophagy. The elevated lysosomal lipase activity, coupled with a decrease in lipid droplet biogenesis, is partially required for the reduction in host lipid content. We propose that KTM consumption stimulates a fasting-like response in the C. elegans intestine by rewiring transcriptional programs to promote lipid utilization. Our results provide mechanistic insight into how the probiotics in Kombucha Tea reshape host metabolism and how this popular beverage may impact human metabolism.